2015
DOI: 10.1109/jlt.2015.2442226
|View full text |Cite
|
Sign up to set email alerts
|

An Optimized Vapor Phase Doping Process to Fabricate Large Core Yb-Doped Fibers

Abstract: The paper demonstrates a standardized process of vapor phase doping to fabricate large core Yb-doped preforms with longer useful length in reproducible manner. The optimization of the process led to successful achievement of Yb-doped core thickness of 4.5 mm (in 14.8 mm of preform diameter) by depositing up to 30 number of core layers with controlled amount of generated precursor vapors. The influence of the process parameters was studied rigorously to enhance the useful preform length up to 380 mm. A combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 26 publications
(40 reference statements)
1
13
0
Order By: Relevance
“…In order to study the particle morphology, Al/Yb-doped soot particles were deposited inside a Heraeus F-300 silica tube (length 300 mm and diameter 20/17 mm) following VPD technique [can be found in details in our earlier publication ref 9 ]. The experiments were carried out at three vapor phase compositions of (i) pure SiO 3 [thd = 2,2,6, 6-tetramethyl-3,5-heptanedionate] were used as precursor materials for Al 2 O 3 and Yb 2 O 3 , respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to study the particle morphology, Al/Yb-doped soot particles were deposited inside a Heraeus F-300 silica tube (length 300 mm and diameter 20/17 mm) following VPD technique [can be found in details in our earlier publication ref 9 ]. The experiments were carried out at three vapor phase compositions of (i) pure SiO 3 [thd = 2,2,6, 6-tetramethyl-3,5-heptanedionate] were used as precursor materials for Al 2 O 3 and Yb 2 O 3 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, conventional solution doping (SD) method depicted several limitations specifically to make large core preforms with homogeneous dopant distribution along the preform length and resulted inadequate process reproducibility . The search for an alternate process led to the development of vapor phase doping (VPD) technique, which demonstrated high reproducibility for producing large core fibers in recent times …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By controlling these parameters judicially, the process reproducibility and dopants uniformity along the preform length could be increased substantially. It also has been reported that incorporation efficiency of Al in silica matrix is much higher than that of Yb .…”
Section: Fabrication Of Optical Fibersmentioning
confidence: 95%
“…[2][3][4] These techniques have been quite successful in embedding RE ions in multitude of optical waveguide structures, such as step, trench, and pedestal refractive-index profiles for specific applications. [5][6][7] Recent developments in spatial division multiplexing (SDM) and multimodal nonlinear pulse propagation have generated renewed interest in optical fibers with graded refractive-index (GRIN) profiles. [8,9] From transmission of information at high spectral efficiency to generation of visible supercontinuum, the multimode passive GRIN fibers are penetrating both in commercial and research space.…”
Section: Introductionmentioning
confidence: 99%